If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2m + -13 + -8(m + -4) = 7m + -1(8m + -3) + -6m + 1 Reorder the terms: -2m + -13 + -8(-4 + m) = 7m + -1(8m + -3) + -6m + 1 -2m + -13 + (-4 * -8 + m * -8) = 7m + -1(8m + -3) + -6m + 1 -2m + -13 + (32 + -8m) = 7m + -1(8m + -3) + -6m + 1 Reorder the terms: -13 + 32 + -2m + -8m = 7m + -1(8m + -3) + -6m + 1 Combine like terms: -13 + 32 = 19 19 + -2m + -8m = 7m + -1(8m + -3) + -6m + 1 Combine like terms: -2m + -8m = -10m 19 + -10m = 7m + -1(8m + -3) + -6m + 1 Reorder the terms: 19 + -10m = 7m + -1(-3 + 8m) + -6m + 1 19 + -10m = 7m + (-3 * -1 + 8m * -1) + -6m + 1 19 + -10m = 7m + (3 + -8m) + -6m + 1 Reorder the terms: 19 + -10m = 3 + 1 + 7m + -8m + -6m Combine like terms: 3 + 1 = 4 19 + -10m = 4 + 7m + -8m + -6m Combine like terms: 7m + -8m = -1m 19 + -10m = 4 + -1m + -6m Combine like terms: -1m + -6m = -7m 19 + -10m = 4 + -7m Solving 19 + -10m = 4 + -7m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '7m' to each side of the equation. 19 + -10m + 7m = 4 + -7m + 7m Combine like terms: -10m + 7m = -3m 19 + -3m = 4 + -7m + 7m Combine like terms: -7m + 7m = 0 19 + -3m = 4 + 0 19 + -3m = 4 Add '-19' to each side of the equation. 19 + -19 + -3m = 4 + -19 Combine like terms: 19 + -19 = 0 0 + -3m = 4 + -19 -3m = 4 + -19 Combine like terms: 4 + -19 = -15 -3m = -15 Divide each side by '-3'. m = 5 Simplifying m = 5
| 7m-(9-4m)=3(m-11) | | Y+3.9=11.8 | | -184=-8(7-8n) | | Y+3.9=11.8 | | 7m-(9-4m)=3(m-11) | | x^2+4x+2.2=0 | | -2m-13-8(m-4)=7m-(8m-3)-6m+1 | | -3d+-28=-40 | | -184=-8(7-8n) | | 16x-14=3(4x-5)+4x+1 | | 7m-(9-4m)=3(m-11) | | 7-2n=n+4 | | 8x+23=-5 | | -2m-13-8(m-4)=7m-(8m-3)-6m+1 | | 8x+23=-5 | | 16x-14=3(4x-5)+4x+1 | | -2m-13-8(m-4)=7m-(8m-3)-6m+1 | | -184=-8(7-8n) | | 7+2(3c+1)=6c+9 | | 7-2n=n+4 | | 7+2(3c+1)=6c+9 | | 7m-(9-4m)=3(m-11) | | 8x+23=-5 | | -2m-13-8(m-4)=7m-(8m-3)-6m+1 | | 2x-5=7x-105 | | 7+2(3c+1)=6c+9 | | 8x+4y+2z=16 | | -218=2r-8(6-4r) | | 8m-3(4-2m)=6(m+1)-2 | | x+2X+2X+2=27 | | -5-(m+8)+6m=4(m+2) | | 2(2x-1)-27= |